PTU-143 Authentication and characterisation of a new oesophageal adenocarcinoma cell line: mfd-1. (22nd June 2015) - Garcia, E; Hayden, A; Cowie, A; Mellone, M; Derouet, M; Duriez, P; Noble, F; White, MJ; Primrose, J; Thomas, G; Fitzgerald, R; Underwood, TJ
Abstract : Introduction: The United Kingdom has the highest age-standardised incidence of oesophageal adenocarcinoma (EAC) in the world. EAC has a narrow window for medical intervention and 2/3 of patients present with incurable disease. Even after potentially curative surgery survival rates are at best 50% at 5 years. The oesophageal International Cancer Genome Consortium (ICGC) is elucidating the genetic landscape of oesophageal adenocarcinoma but the impact of this initiative will only be fully tangible when suitable preclinical models to validate its results become available. We describe the generation and authentication of a novel EAC cell line in a tumour from a 55-year-old male (pT4N3M0) who died from disease recurrence 7 months after neo-adjuvant chemotherapy and oesophagectomy. Method: The MFD-1 cell line was expanded directly from a resected EAC specimen without any recombinant-DNA transformation. Somatic genetic variations (SGV) in DNA from MFD-1, tumour, normal oesophagus, and leucocytes were analysed genome wide with the SNP6 DNA microarray (Affymetrix). WGS was performed in tumour and leucocyte DNA (Illumina). Functional studies of MFD-1 were performed in vitro (3D culture + immunohistochemistry (IHC) + flow cytometry) and in vivo (SCID mouse xenograft). Results: MFD-1 showed 98% concordance with matched tumour on genome wide SNP6 analysis. MFD-1 and the source tumour shared identical SGVs in established cancer promoting genes in EAC including deletions of SMAD4 and p16. A genetic rearrangement in the TP53 gene was observed, consistent with a copy neutral SGV with loss of heterozygosity and a duplication of a mutant TP53 allele, the Arginine 273 Histidine mutation, found in the tumour and the MFD-1 cell line. A second somatic acquired mutation was found in the new EAC candidate DOCK2 gene in the tumour, whilst amplification of a wild type allele was documented in the cell line. In 3D culture, MFD-1 was invasive and proliferative. MFD-1 is Ep-CAM positive (on flow cytometry), and in IHC stains strongly for pan-Cytokeratin and moderately for CK 7, confirming its glandular epithelial phenotype. MFD-1 formed tumours in SCID mice that developed more rapidly than the historical EAC cell lines OE33 and Flo-1. Conclusion: A new tool for the in vitro modelling of EAC has been validated using massive parallel genotyping and sequencing of parent and cell line genomes. A genetic mechanism of malignant transformation operating in the tumour/cell line is consistent with a duplication of a mutant allele in the TP53 gene with a loss of the wild-type allele which translates as a copy neutral SGV with loss of heterozygosity. Disclosure of interest: None Declared.